A Structurable Gel-Polymer Electrolyte for Sodium Ion Batteries - Kim, Jin Il; Choi, Yunah; Chung, Kyung Yoon; Park, Jong Hyeok (WILEY-V C H VERLAG GMBH, 2017)
In this work, a structurable gel-polymer electrolyte (SGPE) with a controllable pore structure that is not destroyed after immersion in an electrolyte is produced via a simple nonsolvent induced phase separation (NIPS) method. This study investigates how the regulation of the nonsolvent content affects the evolving nanomorphology of the composite separators and overcomes the drawbacks of conventional separators, such as glass fiber (GF), which has been widely used in sodium ion batteries (SIBs), through the regulation of pore size and gel-polymer position. The interfacial resistance is reduced through selective positioning of a poly(vinylidene fluoride-co-hexa fluoropropylene) (PVdF-HFP) gel-polymer with the aid of NIPS, which in turn enhances the compatibility between the electrolyte and electrode. In addition, the highly porous morphology of the GF/SGPE obtained via NIPS allows for the absorption of more liquid electrolyte. Thus, a greatly improved cell performance of the SIBs is observed when a tailored SGPE is incorporated into the GF separator through charge/discharge testing compared with the performance observed with pristine GF and conventional GF coated with PVdF-HFP gel-polymer.
Keywords: LITHIUM-ION; PHASE INVERSION; THERMAL-STABILITY; LI-O-2 BATTERY; SEPARATORS; PERFORMANCE; FUTURE; INTERCALATION; CHALLENGES; GRAPHITE